Penentuan Nilai Tekanan Udara Luar Menggunakan Pendekatan Gas Van Der Waals pada Percobaan Hukum Boyle - Defrianto Pratama; Ratu Fenny Muldiani; Kunlestiowati Fenny Hadiningrum; Yunita Citra Dewi (Science and Physics Education Journal (SPEJ), 2025)
Abstract: This study aims to obtain more accurate external air pressure values ​​by applying the Van der Waals equation of state for a Boyle's Law experiment. Pressure data taken from a column of air trapped in a U-tube were analyzed using the ideal gas model and the Van der Waals model. The research findings indicate that the Van der Waals model provides external air pressure values ​​closer to the actual value with a relative error of 0.40%, compared to the ideal gas model, which has a relative error of 10.19%. Therefore, the use of the Van der Waals equation is recommended to improve the accuracy of the Boyle's Law experiment. Based on the research results, it can be concluded that the Van der Waals equation provides a higher level of accuracy than the ideal gas model in determining external air pressure in the Boyle's Law experiment.   Keywords: Boyle's Law, Ideal Gas, Van der Waals Equation, Atmospheric Pressure, Laboratory Experiment.